2002
DOI: 10.1172/jci15318
|View full text |Cite|
|
Sign up to set email alerts
|

Glucose-induced β cell production of IL-1β contributes to glucotoxicity in human pancreatic islets

Abstract: In type 2 diabetes, chronic hyperglycemia is suggested to be detrimental to pancreatic β cells, causing impaired insulin secretion. IL-1β is a proinflammatory cytokine acting during the autoimmune process of type 1 diabetes. IL-1β inhibits β cell function and promotes Fas-triggered apoptosis in part by activating the transcription factor NF-κB. Recently, we have shown that increased glucose concentrations also induce Fas expression and β cell apoptosis in human islets. The aim of the present study was to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
378
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 422 publications
(394 citation statements)
references
References 63 publications
11
378
3
2
Order By: Relevance
“…Increases in islet IL-1␤ during the development of diabetes in an animal model have been reported (7). We reported that specific inhibitors of cyclooxygenase-2 and PGE 2 production prevent IL-1␤ from inhibiting glucose-induced insulin secretion in isolated islets (14).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Increases in islet IL-1␤ during the development of diabetes in an animal model have been reported (7). We reported that specific inhibitors of cyclooxygenase-2 and PGE 2 production prevent IL-1␤ from inhibiting glucose-induced insulin secretion in isolated islets (14).…”
Section: Discussionmentioning
confidence: 75%
“…Long term exposure to high glucose conditions inhibits endothelial cells from responding to cytokine exposure with an increase in GCL expression and activity (3). That the pathogenesis of diabetes mellitus involves interactions with IL-1␤ and oxidative stress secondary to chronic hyperglycemia (6,7) raises the questions of whether GCL is normally expressed in the islet and whether overexpression of GCL protects the beta cell from oxidative stress.…”
mentioning
confidence: 99%
“…Fas (CD95) is a cell surface receptor that plays a central role in the regulation of death in many cell types, including ␤ cells, and may be implicated in the development of type 1 and type 2 diabetes (3)(4)(5). Glucose-induced ␤ cell apoptosis in human islets involves IL-1␤-mediated up-regulation of Fas and subsequent interaction with the constitutively expressed Fas ligand (FasL) on neighboring ␤ cells (3,(6)(7)(8). Fas/FasL interaction leads to cleavage of procaspase-8, the most upstream caspase in the Fas apoptotic pathway.…”
mentioning
confidence: 99%
“…Interestingly, in ␤ cells NF-B activation can also be triggered by glucose (6,13). Increasing evidence points to noninflammatory effects of NF-B, including regulation of insulin secretion (14,15).…”
mentioning
confidence: 99%
“…Furthermore, it is becoming increasingly apparent that many factors classically deemed type 1 diabetesspecific are also integral to the process of ␤ cell failure in type 2 diabetes patients. These include the effect of IL-1␤, Fas, and nuclear factor-B, endoplasmic reticulum stress, and increased expression of c-Myc (19)(20)(21)(22). Interestingly, polymorphisms in the Fas pathway have been associated recently with type 2 diabetes (23).…”
mentioning
confidence: 99%